Prevalence of work-related musculoskeletal disorders among hairdressers - Happiness Anulika Aweto (International Journal of Occupational Medicine and Environmental Health, 2015)
Objectives: This study has investigated the prevalence of work-related musculoskeletal disorders (WMSDs), the most commonly affected body parts, the risk factors of WMSDs and the coping strategies adopted by hairdressers. Material and Methods: The study design was a cross-sectional descriptive survey design. Two hundred and ninety-nine hairdressers (242 females and 57 males) from salons in Surulere and Mushin Local Government Areas of Lagos State completed a 27-item questionnaire. They were selected using a non-probability consecutive sampling technique. The inferential analysis was conducted using the Chi2 test. The level of significance stood at p < 0.05. Results: The 12-month prevalence of musculoskeletal disorders stood at 75.6%. Two hundred and twenty-one (91.3%) participants reported gradual onset of musculoskeletal disorders. One hundred and sixteen (47.9%) participants had the onset of the WMSDs at the age range of 26–35 years. The most commonly affected body parts included the low back (76.3%), shoulder (62.5%) and neck (46.3%). Some of the major job risk factors of the WMSDs that were identified included: working in the same position for long periods and attending to a large number of customers in 1 day. Taking sufficient rest breaks by participants was one of the coping strategies adopted by the participants. The mean number of years of working experience was 7.85±0.4 years. One hundred and twenty-four (41.5%) participants had worked for 1–5 years. The Chi2 analysis showed that the prevalence of musculoskeletal disorders were significantly associated with the age of a participant (Chi2 = 78.78, p = 0.001), years of working experience (Chi2 = 78.03, p = 0.001) and hours spent working in a standing position (Chi2 = 8.77, p = 0.01), respectively. Conclusions: The age of hairdressers, their years of working and the long hours they spent working in a standing position may be significant factors that contribute to the high prevalence of the WMSDs among them. The most commonly affected body parts included the low back, shoulders and neck.